A conceptual framework of sales forecast : in business processes dependent on the actual location of sales with analysis of past data and coming information about future days from valid online resources - Majidi, Alireza (2019)
Dissertation presented as partial requirement for obtaining the Master’s degree in Information Management, specialization in Information Systems and Technologies Management